Labour Market Participation in Brazil: A Discrete Game Approach - Marcelo Resende; Vicente Cardoso (Center for Economic Studies and ifo Institute (CESifo), 2017)
The paper aims to investigate the labour market participation of couples in Brazil in 2013. The observed endogenous variables portraying participation are assumed to be the outcome of a static discrete game between the partners. Different solution concepts are considered (Nash, Stackelberg and imposed Pareto optimality), and the estimations are implemented for rural and urban areas. The evidence, in comparison with previous evidence for more developed and homogeneous countries, displays qualitative similarities in terms of own wage, cross wage and age effects and a stronger inhibiting role of the number of small children in the case of the female partner. In particular, cross-wage effects also indicated gender asymmetry. Additionally, one identifies a more limited role of schooling on labour market participation in rural areas and gender contrasts in terms of the number of persons in the household that have a positive significant effect only for male partners.
Keywords: J21; 330; labour market participation; discrete game; Brazil